Advertisement Remove all ads

Integrate the following w.r.t. x (x3-3x+1)/sqrt(1-x2) - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Integrate the following w.r.t. x `(x^3-3x+1)/sqrt(1-x^2)`

Advertisement Remove all ads

Solution

`(x^3-3x+1)/sqrt(1-x^2)=−(x^2+3x−1+1−1)/sqrt(1−x2)`

`=−(1-x^2+3x−2)/sqrt(1−x2)`

`=(−1−x^2)/sqrt(1−x^2)−(3x−2)/sqrt(1−x^2)`

 

`=−sqrt(1−x2)−(3x−2)/sqrt(1−x2)`

`=>int(x^3-3x+1)/sqrt(1-x^2)dx`

`=int(−sqrt(1−x2)−(3x−2)/sqrt(1−x2))dx`

`=−intsqrt(1−x2)dx−int(3x−2)/sqrt(1−x2)dx`

`=−intsqrt(1−x2)dx−int(3x)/sqrt(1−x2)dx-2int(1)/sqrt(1−x2)dx`

`=−intsqrt(1−x2)dx−int(3x)/sqrt(t)dt-2int(1)/sqrt(1−x2)dx    (Here, t=1−x2.)`

 

`=−[1/2xsqrt(1−x2)+1/2sin^(−1) x]+3/2xx2sqrtt−2cos^(−1) x+C `

`= −1/2xsqrt(1−x2)−1/2sin^(−1) x+3sqrt(1−x2)−2cos^(−1) x+C`

 

Concept: Evaluation of Simple Integrals of the Following Types and Problems
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×